Identification of xylan arabinosyl 2‐O‐xylosyltransferases catalyzing the addition of 2‐O‐xylosyl residue onto arabinosyl side chains of xylan in grass species. (5th September 2022) - Zhong, Ruiqin; Lee, Chanhui; Cui, Dongtao; Phillips, Dennis R.; Adams, Earle R.; Jeong, Ho‐Young; Jung, Ki‐Hong; Ye, Zheng‐Hua
SUMMARY: Grass xylan, the major hemicellulose in both primary and secondary cell walls, is heavily decorated with α‐1, 3‐linked arabinofuranosyl (Ara f ) residues that may be further substituted at O ‐2 with xylosyl (Xyl) or Ara f residues. Although xylan 3‐ O ‐arabinosyltransferases (XATs) catalyzing 3‐ O ‐Ara f addition onto xylan have been characterized, glycosyltransferases responsible for the transfer of 2‐ O ‐Xyl or 2‐ O ‐Ara f onto 3‐ O ‐Ara f residues of xylan to produce the Xyl‐Ara f and Ara f ‐Ara f disaccharide side chains remain to be identified. In this report, we showed that a rice GT61 member, named OsXAXT1 (xylan arabinosyl 2‐ O ‐xylosyltransferase 1) herein, was able to mediate the addition of Xyl‐Ara f disaccharide side chains onto xylan when heterologously co‐expressed with OsXAT2 in the Arabidopsis gux1/2/3 ( glucuronic acid substitution of xylan 1/2/3 ) triple mutant that lacks any glycosyl substitutions. Recombinant OsXAXT1 protein expressed in human embryonic kidney 293 cells exhibited a xylosyltransferase activity catalyzing the addition of Xyl from UDP‐Xyl onto arabinosylated xylooligomers. Consistent with its function as a xylan arabinosyl 2‐ O ‐xylosyltransferase, CRISPR‐Cas9‐mediated mutations of the OsXAXT1 gene in transgenic rice plants resulted in a reduction in the level of Xyl‐Ara f disaccharide side chains in xylan. Furthermore, we revealed that XAXT1 close homologs from several other grass species, including switchgrass, maize, and Brachypodium, possessed the same functions as OsXAXT1, indicating functional conservation of XAXTs in grass species. Together, our findings establish that grass XAXTs are xylosyltransferases catalyzing Xyl transfer onto O ‐2 of Ara f residues of xylan to form the Xyl‐Ara f disaccharide side chains, which furthers our understanding of genes involved in xylan biosynthesis. Significance Statement: Grass xylan can be substituted at O ‐3 with 2‐ O ‐Xyl‐Ara f disaccharide side chains in which the Ara f residue may be further esterified with hydroxycinnamates. We showed that a rice GT61 glycosyltransferase is a xylosyltransferase catalyzing xylosyl transfer onto Ara f side chains of xylan, which contributes to our understanding of the biochemical mechanisms underlying the complex substitutions of grass xylan.